Power converter's optimisation and design. Discrete cost function with genetic based algorithms - Helali, H.; Bergogne, D.; Ben Hadj Slama, J.; Morel, H.; Bevilacqua, P.; Allard, B.; Brevet, O. (2005 European Conference on Power Electronics and Applications : 11-14 September 2005, 2005)
A genetic algorithm with discrete cost functions is used to design and optimise a 42 V-14 V/8 A buck converter. The use of discrete and continuous cost functions are confronted. Discrete cost functions produces better designs. Electrical time domain simulation is used for verification. Experimental measurement, electrical and thermal, validates the design.